RETRACTION NOTICE TO "Exploring Unconventional Paths: Narratives of Science Appreciation Among Non-STEM Students" - Honra, Joelash R. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This article entitled “Exploring Unconventional Paths: Narratives of Science Appreciation Among Non-STEM Students” (2024), authored by Joelash R. Honra & Edwin R. Arboleda, published in Vol. 5, No. 1 of International Journal of Multidisciplinary: Applied Business and Education Research. 5(1), 216 – 235 has been retracted as requested by the authors.